The Project Manager â€œLanguageâ€ in a Crisis Scenario - Di Lorenzo , Daniele (European Scientific Journal, ESJ, 2021)
A pandemic scenario may add time and space limits to the relationships that exist between people and businesses. It is reasonable to assume that multiple projects are conditioned by those limitations. As a result, they should follow the same constraints. Two fundamental views that project managers should focus on during the management of projects are the technical-operative modalities they use to advance the activities and their mindset to manage their dynamics. The union of these two dimensions can be regarded as the â€œlanguageâ€ of project managers. This paper focuses on analyzing the impacts of pandemics on these dimensions and the ways through which these conditions could change the â€œlanguageâ€ to properly react to this kind of crisis. As argued here, the variables of â€œtriadâ€ (Reaction-ExecutionResults) combined with an appropriate mindset and the usage of a micro-goal approach could be an effective reply to a pandemic.